P263 Influence of Crohn′s Disease phenotype in the retention rate of ustekinumab treatment: SUSTAIN Study. (27th May 2021) - Chaparro, M; Bastón Rey, I; Fernández-Salgado, E; González García, J; Ramos, L; Diz-Lois Palomares, M T; Argüelles, F; Iglesias Flores, E; Cabelo, M; Rubio Iturria, S; Núñez Ortiz, A; Charro, M; et al.
Abstract: Background: Crohn′s disease (CD) is a progressive inflammatory bowel disease that can lead to complications such as strictures or penetrating disease, and ultimately surgery, representing a complex clinical challenge in the care of patients. We aimed to evaluate the influence of CD phenotype in the retention rate of ustekinumab in the Sustain study. Methods: Retrospective, multicentre study (>60 sites) including patients with active CD [(Harvey-Bradshaw (HBI)>4)] who received ≥1 dose of ustekinumab intravenously before July 2018. Clinical remission was defined as HBI≤4 and response as ≥3 points decrease from baseline. Loss of response (LoR) was defined as reappearance of symptoms that led to intensifying the treatment dose, adding another medication to control CD, switching or surgery in patients with short-term remission. Disease characteristics were collected (date of diagnosis; location; behaviour: inflammatory, stenosing or penetrating; presence of perianal disease or extraintestinal manifestations; previous surgeries, etc.). The retention rates in patients on ustekinumab depending of their disease phenotype were evaluated by descriptive analysis and Kaplan-Meier survival curves. Survival curves were compared using the log-rank test. Predictive factors were assessed by Cox-regression. Data quality was assured by remote monitoring. Results: 463 CD patients were included (Table 1). 87 patients (18.6%) had penetrating CD in our cohort. The probability of maintaining UST treatment was 91% at 6, 83% at 12, 76% at 18 and 73% at 24 months. Similar retention rates were observed in patients with inflammatory (77.6%), stricturing (76.4%) and penetrating (79%) disease behaviour (p>0.05). Figure 1. Conclusion: Ustekinumab has shown to be equally effective in the treatment of inflammatory, stricturing and penetrating CD phenotype in Sustain, the largest study evaluating its use in CD in clinical practice, having the longest follow-up period reported to date.